Judicial Review of the Obligation to Have an Approval Letter for Sailing in the Crime of Sailing in Indonesia - Rifai, Anis; Maguchu, Prosper (Universitas Kuningan, 2024)
Shipping is controlled by the state and carried out by the government. Sailing approval letters can be given by a harbour master to the ship user or owner if the ship has fulfilled several important requirements. The aim of research is to find out how the obligation of a sailing approval letter is regulated and what the legal consequences of not having a sailing approval letter are. Research methods used a normative juridical method with analytical descriptive specifications. The results of the research found that ship sailing is required to have a Sailing Approval Letter issued by the Harbormaster as stated in article 219, paragraph (1), of Law Number 17 of 2008 concerning Shipping. Conclusion: The legal consequences if you do not have a letter of approval from the harbormaster will be threatened with imprisonment and fined as regulated in Article 323 Paragraph (1) of Law Number 17 of 2008 concerning Shipping and Law Number 8 of 1981 concerning Criminal Procedure Law, as well as statutory regulations.